Cystic lesions of the retrorectal space. Issue 2 (24th August 2022) - Brown, Ian S; Sokolova, Anna; Rosty, Christophe; Graham, Rondell P
Abstract : Cysts of the retrorectal space comprise a heterogeneous group of rare lesions. Most develop from embryological remnants and include tailgut cysts, dermoid cysts, rectal duplication cysts, anal canal duplication cysts, sacrococcygeal teratomas and anterior meningocoele. Tailgut cyst is the most common cyst of developmental origin, usually presenting as a multilocular cystic mass with mucoid content and lined by multiple epithelial types. Compared with tailgut cysts, rectal duplication cysts display all layers of the large bowel wall including a well‐defined muscularis propria. Retrorectal cysts of non‐developmental origin are far less common and represent lesions that either infrequently involve the retrorectal space or undergo extensive cystic change. This review provides an overview of the various histological types of cystic lesions of the retrorectal space, divided into cysts of developmental origin and those of non‐developmental origin. A practical pathological and multidisciplinary approach to diagnosing these lesions is presented. Abstract : Pathological features of retrorectal cysts.